Analisis Struktur Gerak Ibing Jagatraharja di Padepokan Fajar Kancana Kumpay Kuning Putra Desa Nagarakembang Kabupaten Majalengka - Tika Rostika; Arni Apriani; Budi Dharma (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
This study aims to analyze one of the movements that is characteristic of Padepokan Fajar Kancana Kumpay Kuning Putra in Nagarakembang Village, Majalengka Regency, namely the Ibing Jagatraharja movement. Ibing Pencak Silat can be interpreted as a basic martial arts movement presented in the form of dance or the development of the pencak silat martial arts movement. The form of the Jagatraharja Movement is a development of core movements such as Tonjok, Nahan, and Siku Ajul. The problem raised in this study is to describe the structure of the Ibing Jagatraharja movement. The purpose of this study is to describe the structure of the movement of Ibing Jagatraharja Padepokan Fajar Kancana Kumpay Kuning Putra. This study uses a qualitative method with a descriptive approach with data collection techniques of observation, interviews and documentation.